Digitalisasi Al-Qur’an dalam Perspektif Historis: Transformasi Mushaf ke Format Elektronik dan Implikasinya bagi Umat Islam - Afhan, Adib (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The digitalization of the Qur’an has brought significant changes to society in the modern technological era. Through digital mushaf applications with various available features, Muslims can access and read the Qur’an anytime and anywhere with greater convenience. This study discusses the development of the Qur’anic mushaf up to the digital era, the characteristics of electronic Qur’anic manuscripts, and their impact on the lives of contemporary Muslims. The type of research used is library research with a qualitative descriptive analysis approach, by collecting data and materials related to the theme and issues discussed from various library sources. The results of the study show that the digitalization of the Qur’an provides convenience and serves as a practical solution, especially for the millennial and Gen Z generations who are accustomed to technology. However, its use must still be carried out wisely, without abandoning the tradition of reading the printed mushaf. By maintaining this balance, the use of digital Qur’an applications can provide maximum benefits without diminishing the sacredness and reverence of the Qur’an.